2004
DOI: 10.1007/s00493-004-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

The Diameter of a Scale-Free Random Graph

Abstract: We consider a random graph process in which vertices are added to the graph one at a time and joined to a fixed number m of earlier vertices, where each earlier vertex is chosen with probability proportional to its degree. This process was introduced by Barabási and Albert [3], as a simple model of the growth of real-world graphs such as the world-wide web. Computer experiments presented by Barabási, Albert and Jeong [1,5] and heuristic arguments given by Newman, Strogatz and Watts [23] suggest that after n st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
488
0
11

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 490 publications
(506 citation statements)
references
References 22 publications
7
488
0
11
Order By: Relevance
“…In [5], it was proved that in the PAM and for δ = 0, for which τ = 3, the diameter of the resulting graph is equal to log t log log t (1 + o (1)). Unfortunately, the matching result for the CM has not been proved, so that this does not allow us to verify whether the models have similar distances.…”
Section: Discussion and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In [5], it was proved that in the PAM and for δ = 0, for which τ = 3, the diameter of the resulting graph is equal to log t log log t (1 + o (1)). Unfortunately, the matching result for the CM has not been proved, so that this does not allow us to verify whether the models have similar distances.…”
Section: Discussion and Related Workmentioning
confidence: 99%
“…because, when N → ∞, 5) so that, whp, N (1) = ∅. For some constant C > 0, which will be specified later, and k ≥ 2 we define recursively…”
Section: And the Bound On L N In (23) Into (24) Gives Us That The Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Many well-known models for complex networks, including the preferential attachment model by Barabási and Albert [5], have diameters growing at most logarithmically with time. (In fact, in [8] Bollobás and Riordan showed that a.a.s. the diameter of the preferential attachment model is asymptotic to log t/ log log t.) Consider a graph G t produced by the SPA model.…”
Section: Directed Diametermentioning
confidence: 99%
“…One rigorous approach is due to [3]. They introduced a random multigraph which is built of random forests which are then formed into multigraphs by partitioning the vertex set and identifying vertices in the same block of the partition.…”
Section: Introductionmentioning
confidence: 99%